The Role of HIV/AIDS Cadre on Improving Quality of Life among Women with HIV/AIDS in a Community Setting: A Qualitative Study - Ernawati, Ernawati; Nursalam, Nursalam; Devy, Shrimarti Rukmini (International Journal of Psychosocial Rehabilitation, 2020)
In responding to the AIDS epidemic in Indonesia, HIV/AIDS cadres have been formed derived from various elements of society, but their role is still below the optimal target to support for care, physical and psychosocial mildness of vulnerable women with HIV/AIDS. The aim was to explore the experience of of the role of HIV/AIDS cadres on improving quality of life among women living with HIV/AIDS in a community setting. A qualitative research method through a case study approach was conducted in some areas where HIV/AIDS cadres have formed such as: Cirebon West Java, Kudus, and Jepara district of Central Java, Indonesia. A purposive sampling method was applied to recruit the participants. In-depth interview was undertaken with 15 participants using a set of semi-structured questions about: “what HIV/AIDS cadres have been done to date, what skills they must conquer on and how the surrounding supported response”. Thematic content analysis using manual combine an inductive approach. Fives themes were identified which described respondents’ experiences such as: roles as cadre, cadre skills, harmonization with healthcare providers, community response and motivation become a cadre. This study also identified that HIV/AIDS cadres were significantly supporting people with HIV/AIDS in term of acceptance, against the stigma and discrimination in the community. Participants assessed the quality of life among women with HIV/HIV to have improved gradually post accompaniment. However, participants also faced complexity problems and resistance from the community. Cadres’ self-capacity needs to be improved through standardized training to improve their competencies and skills before they implement accompaniment to women with HIV/AIDS in the community.